2013
DOI: 10.7314/apjcp.2013.14.11.6513
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome with Brachytherapy for Recurrent Nasopharyngeal Carcinoma

Abstract: Background: To evaluate the treatment outcome and major late complications of all patients with recurrent nasopharyngeal carcinoma (NPC) treated with intracavitary brachytherapy (ICBT) in Hospital Kuala Lumpur. Materials and Methods: This retrospective study was conducted at the Department of Radiotherapy and Oncology, Hospital Kuala Lumpur, Malaysia. All patients with histologically confirmed recurrent NPC in the absence of distant metastasis treated in the period 1997-2010 were included in this study. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Brachytherapy is the most used modality for small local failures. Cheah et al [23] retrospectively reviewed the outcome of 33 patients treated with brachytherapy. The 5-year local disease free interval was 45% and overall survival was 28%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachytherapy is the most used modality for small local failures. Cheah et al [23] retrospectively reviewed the outcome of 33 patients treated with brachytherapy. The 5-year local disease free interval was 45% and overall survival was 28%.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the cumulative dose toxicity makes side effects the limiting factor, i.e. brain necrosis, cranial nerve palsy and endocrine dysfunction [23]. Brachytherapy is the most used modality for small local failures.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, EBRT remains a main treatment method to be used. Many authors combined external RT with a localized boost (using brachytherapy or SRS/FSRT) to achieve high tumor dose with better sparing of adjacent organs at risk [8,9]. Qiu et al [8] in a retrospective study reported the result of different reirradiation techniques for local recurrence NPC, 168 patients were treated with four different irradiation modalities (3D-CRT, IMRT, BT, and BT with external radiotherapy), and 43% have received brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Age, histology, recurrence T-classification, and interval to recurrence were factors for overall survival [1,8,13]. Several publications reported the lymph node spread and reirradiation dose are one of the most important factors for local-regional progression after the salvage treatment [9,4,15]; the general consensus is that reirradiation dose above 60 Gray (Gy) is needed for effective salvage [2]. Brachytherapy is an option for treating located small tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation